A Study On the Effect of Citrulline Concentrations On In-Vitro Sperm Motility in Diabetic Infertile Male - Kalaiselvi S; Syed Ali M; Anuradha V; Subhashini A (International Journal of Pharma and Bio Sciences, 2023)
The worldwide prevalence of diabetes mellitus (DM) is gradually rising, which impacts reproductive systems, particularly sperm motility. Bio-molecules have been found to improve sperm motility in both in-vitro and in-vivo settings, thereby enhancing the effectiveness of Assisted Reproductive Technology (ART). Watermelon seeds naturally contain a significant amount of citrulline, which has been shown to improve sperm motility in animal models. Therefore, this randomized controlled study aimed to analyze the effect of watermelon seed extract and commercially available citrulline on in-vitro sperm motility in diabetic infertile males. Citrulline was extracted from watermelon seeds, and commercially available citrulline from Sigma was used. The extracted citrulline was quantified using HPLC. Infertile males were allocated randomly into two groups based on their sugar levels. Semen parameters, including motility, were assessed at baseline. The participants' sperm samples were treated with various concentrations (0.01-0.05 ml) of watermelon seed extract and commercial citrulline. Sperm motility was assessed in all semen samples treated with citrulline at 30-minute intervals for 2 hours. The HPLC analysis revealed that citrulline in the crude and purified watermelon extracts were 5 mg/g and 28 mg/g, respectively. The mean total sperm motility of group 1 and group 2 participants at baseline, was 41.5% and 37.7%, respectively. Sperm motility was improved in all concentrations of watermelon seed extract and commercial citrulline. However, the regression models showed that group 2 participants had a lower percentage of sperm motility than group 1 participants, even after treatment with watermelon seed extract and commercial citrulline solution. In conclusion, the study found that citrulline treatment improved in-vitro sperm motility in the study population, suggesting that citrulline could be a potential in-vitro sperm enhancer.